Characteristics and outcomes associated with 30-day readmissions following acute coronary syndrome 2000–2013: the Acute Coronary Syndrome Israeli Survey. Issue 8 (December 2019) - Litovchik, Ilia; Pereg, David; Shlomo, Nir; Vorobeichik, Dina; Beigel, Roy; Iakobishvili, Zaza; Vered, Zvi; Goldenberg, Ilan; Minha, Sa'ar
Background: Readmissions following acute myocardial infarction are associated with poor outcomes and a heavy economic burden. There are few evidence-based data on the characteristics and outcomes of patients readmitted following acute coronary syndrome. We explored the incidence and outcomes of patients readmitted after an acute coronary syndrome in the past decade. Methods: The study population comprised all acute coronary syndrome patients who were enrolled and prospectively followed up in the biennial Acute Coronary Syndrome Israeli Survey from 2000 to 2013. Multivariate analysis identified factors independently associated with readmission and long-term mortality. Results: There were 13, 010 study patients, of whom 556 (4.2%) had an unplanned readmission within 30 days of the index event. Stent thrombosis during the index hospitalisation (odds ratio (OR) 8.43; 95% confidence interval (CI) 4.11–16.07; P <0.001), female sex (OR 1.34; 95% CI 1.1–1.63; P =0.003), older age (>65 years; OR 1.28; 95% CI 1.06–1.55; P =0.011), and lack of dual-antiplatelet therapy (OR 1.52; 95% CI 1.25–1.86; P <0.001) were independently associated with readmission. Readmitted patients were less likely to have been treated with guideline-directed medical therapy during hospitalisation and at discharge, and were less likely to have undergone coronary angiography. A strong trend towards decline in readmission rates following acute coronary syndrome was observed between 2000 and 2013 ( P <0.001). However, the association between readmission and poor long-term outcome was more pronounced among patients readmitted during more recent years (2008–2013). Conclusions: Patients readmitted to hospital following acute coronary syndrome comprise an undertreated, high-risk cohort. Our findings indicate that despite a significant decline in readmission rates following acute coronary syndrome over the past decade, readmission within 30 days following acute coronary syndrome still portends a grave outcome.